Measurement of brainstem diameter in small-breed dogs using magnetic resonance imaging - Kim, Jihyun; Kwon, Danbee; Kim, Sung-Soo; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2023)
Measurement of brainstem diameters (midbrain, pons, and medulla oblongata) is of potential clinical significance, as changes in brainstem size may decrease or increase due to aging changes, neurodegenerative disorders, or neoplasms. In human medicine, numerous studies have reported the normal reference range of brainstem size, which is hitherto unexplored in veterinary medicine, particularly for small-breed dogs. Therefore, the purpose of this study is to investigate the reference range of brainstem diameters in small-breed dogs and to correlate the measurements with age, body weight (BW), and body conditions score (BCS). Herein, magnetic resonance (MR) images of total 544 small-breed dogs were evaluated. Based on the exclusion criteria, 193 dogs were included in the midbrain and pons evaluation, and of these, 119 dogs were included in medulla oblongata evaluation. Using MR images, height and width of the midbrain, pons, and medulla oblongata was measured on the median and transverse plane on T1-weighted image. For medulla oblongata, two points were measured for each height and width. The mean values of midbrain height (MH), midbrain width (MW), pons height (PH), pons width (PW), medulla oblongata height at fourth ventricle level (MOHV), medulla oblongata height at cervicomedullary (CM) junction level (MOHC), rostral medulla oblongata width (RMOW), and caudal medulla oblongata width (CMOW) were 7.18±0.56 mm, 17.42±1.21 mm, 9.73±0.64 mm, 17.23±1.21mm, 6.06±0.53 mm, 5.77±0.40 mm, 18.93±1.25 mm, and 10.12±1.08 mm, respectively. No significant differences were found between male and female dogs for all the measurements. Negative correlation was found between age and midbrain diameter including MH (p < 0.001) and MW (p = 0.002). All brainstem diameters were correlated positively with BW (p < 0.05). No significant correlation was found between BCS and all brainstem diameters. Brainstem diameters differed significantly with breeds (p < 0.05), except for MW (p = 0.137). We suggest that these results could be useful in assessing abnormal condition of the brainstem in small-breed dogs.